The subbasement membrane distribution of type IV collagen in normal human skin - Kobayashi, H; Ishii, M; Chanoki, M; Fukai, K; Hamada, T; Muragaki, Y; Ooshima, A (Journal of dermatology, 1989)
Samples of normal human skin were obtained from 48 sites in 26 subjects ranging in age from 2 to 85 years. The samples were examined by indirect immunofluorescence and immunoelectron microscopy using anti-human type IV collagen antibodies produced by immunizing rabbits with type IV collagen extracted from human placenta. Fluorescence was observed as granular or fine fibrous patterns, not only in the basement membrane at the dermo-epidermal junction, around the vessels, and the accessory organs of the skin, but also in the dermal regions in the vicinity of the basement membranes. This suggests the presence of type IV collagen in the dermis deep to the basement membrane. Ultrastructurally, the extrabasal lamina distribution of type IV collagen was noted as a partial distribution around the fibroblasts that existed close to the basal lamina. These findings are considered to be important in examining the function of this collagen in the dermis and the dynamics and metabolism of the basement membrane under normal and abnormal conditions.